Quo Vadis Education Administration at Madrasah Diniyah in Indonesia - Hamdanah Hamdanah (AL-ISHLAH: Jurnal Pendidikan, 2022)
This paper is a paper-based on literature review with field studies. This paper has three critical questions. First, what is the concept of education administration study? Second, how is the course of Madrasah Diniyah in Indonesia? and third, what about Quo Vadis education administration at Madrasah Diniyah in Indonesia? by using a content analysis approach to explain the concept of education administration and the ideas of Madrasah Diniyyah and Quo Vadis education administration at Madrasah Diniyyah in Indonesia. The results of this study are first to know the concept of education administration and secondly to the idea of Madrasah Diniyyah in Indonesia and the third Quo Vadis of education administration in Madrasah Diniyyah in Indonesia.